Two dimensions (2D) and three dimensions (3D) of slope stability analysis by using plaxis software - Nur Azniza Zulkifli, 1995-, author 614103; Nazri Ali supervisor 182241; Fakulti Kejuruteraan Awam 8022 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam) - Universiti Teknologi Malaysia, 2018